Signal-to-interference ratio improvement by using a phased array antenna of switched-beam elements - Ngamjanyaporn, Phaisan; Phongcharoenpanich, Chuwong; Akkaraekthalin, Prayoot; Krairiksh, Monai (My University, 2005)
A phased array antenna of switched-beam elements is proposed to improve the signal-to-interference ratio (SIR). By using 1-bit phase shifters, the main beam of the array is switched to desired signal direction, and with the switched-beam patch antenna elements the null patterns are changeable. The results of radiation patterns show that the interference suppression can be improved. Moreover, the SIR measurement is also set up in multipath environment to ensure the array performance. It is found that the SIR is significantly affected by the multipath environment; however, the SIR improvement of more than 10 dB can be obtained by changing the null patterns. © 2005 IEEE.
Keywords: 1-bit phase shifter; Patch antenna; Phased array antenna; PIN diode; Signal-to-interference ratio (SIR); Switched-beam antenna